Association between potentially inappropriate medications at discharge and unplanned readmissions among hospitalised elderly patients at a single centre in Japan: a prospective observational study - Junpei Komagamine; Taku Yabuki; Masaki Kobayashi (BMJ Open)
Objective To determine the prevalence of potentially inappropriate medication (PIM) use at admission and discharge among hospitalised elderly patients and evaluate the association between PIMs at discharge and unplanned readmission in Japan.Design A prospective observational study conducted by using electronic medical records.Participants All consecutive patients aged 65 years or older who were admitted to the internal medicine ward were included. Patients who were electively admitted for diagnostic procedures were excluded.Main outcome measures The primary outcome was 30-day unplanned readmissions. The secondary outcome was the prevalence of any PIM use at admission and discharge. PIMs were defined based on the Beers Criteria. The association between any PIM use at discharge and the primary outcome was evaluated by using logistic regression.Results Seven hundred thirty-nine eligible patients were included in this study. The median patient age was 82 years (IQR 74–88); 389 (52.6%) were women, and the median Charlson Comorbidity Index was 2 (IQR 0–3). The proportions of patients taking any PIMs at admission and discharge were 47.2% and 32.2%, respectively. Of all the patients, 39 (5.3%) were readmitted within 30 days after discharge for the index hospitalisation. The use of PIMs at discharge was not associated with an increased risk of 30-day readmission (OR 0.93; 95% CI 0.46 to 1.87). This result did not change after adjusting for patient age, sex, number of medications, duration of hospital stay and comorbidities (OR 0.78; 95% CI 0.36 to 1.66).Conclusion The prevalence of any PIM use at discharge was high among hospitalised elderly patients in a Japanese hospital. Although the use of PIMs at discharge was not associated with an increased risk of unplanned readmission, given a lack of power of this study due to a low event rate, further studies investigating this association are needed.Trial registration number UMIN000027189.